Pathological characteristics of the wound bed at engraftment full thickness transplant - S. B. Bogdanov; E. A. Terman; Y. A. Bogdanova (Кубанский научный медицинский вестник, 2016)
Developed surgical methods of surgical treatment of deep burns, creating conditions for engraftment full thickness transplant on purulent wound. Studied the pathological aspects of the wound bed after excision of granulation and wound edges during engraftment full thickness transplant in 5 patients. Investigations of the fibrous layer of granulation tissue.